Prolonged treatment planning can increase real rectal dose in 3D brachytherapy for cervical cancer - Vlachová, Zuzana (J Contemp Brachytherapy, 2020)
PURPOSE: The purpose of this study was to evaluate the influence of 3D brachytherapy planning time on the real dose distribution. MATERIAL AND METHODS: 10 patients with cervical cancer were evaluated using 2 computed tomography (CT) scans brachytherapy. The first scan was performed after the insertion of UVAG applicators, and the second was done after creating the treatment plan, just before the irradiation of first and third fraction. Both plans were compared in terms of changes of volumes and differences in the dose for high-risk organs using GEC-ESTRO Working Group parameters. RESULTS: The median planning time was 54 minutes (36-64 minutes). The absolute median change of volume for bladder, rectum, and sigmoid was 32.1 cm(3) (1.6-108.6 cm(3)), 5.6 cm(3) (0.4-61.8 cm(3)), and 8.4 cm(3) (0.2-74.1 cm(3)), respectively. This difference led to an increased dose for bladder and sigmoid for D(0.1cc) by 46.7 cGy and 25.7 cGy, for D(1cc) by 59.2 cGy and 11.8 cGy, and for D(2cc) by 44.7 cGy and 10 cGy, respectively, per each fraction. Measured volume change in case of rectum led to a decreased dose per each fraction for D(0.1cc) with 7.1 cGy, for D(1cc) with 3.5 cGy, and for D(2cc) with 4.8 cGy. We observed that statistically significant dependency between the planning time and the dose was proved for rectum. The longer time for planning, the higher dose for rectum. The correlation coefficient for D(0.1cc) was 0.6715 (p = 0.0061), for D(1cc) was 0.6404 (p = 0.011), and for D(2cc) was 0.5891 (p = 0.0197). CONCLUSIONS: Extended treatment planning time for brachytherapy due to the changes in topography of small pelvis can lead to different dose in high-risk organs than previously planned. It seems that the most significant changes are related to rectum.